Pulp-test responses in orthodontic patients - Cave S. G.; Freer T. J.; Podlich H. M. (Sciendo, 2002)
The diagnosis of orofacial pain is complicated in the orthodontic patient as treatment-induced alterations to pulpal physiology may result in altered responses to pulp-test stimuli. Thirty-three subjects commencing fixed orthodontic treatment and another 15 subjects not undergoing orthodontic treatment were used in this study. Cold and electrical stimuli were applied to the maxillary incisor teeth prior to treatment, after the placement of fixed appliances and at regular intervals for both groups for up to 252 days. At baseline, response thresholds to electric testing were typically higher for orthodontic subjects, particularly for the lateral incisors. For the non-orthodontic group, the response threshold over the 252 days was relatively constant. For the orthodontic group, application of force immediately increased the response threshold to electric pulp testing, which peaked after two months. By day 252, response means for lateral incisors still remained elevated. Responses to thermal testing were more consistent and reliable. The results of this study indicate that dental practitioners should interpret responses to electric pulp testing cautiously in orthodontic patients and that thermal testing with carbon dioxide snow may be more reliable.